Effect of Abdominal Draw-in Maneuver Using Breathing on Transversus Abdominis Thickness and Trunk Control in Stroke Patients - Jeongil Kang; Youngjun Moon (Journal of International Academy of Physical Therapy Research, 2021)
Background: To restore the trunk function of stroke patients who tend to experience trunk weakness, a single exercise intervention is usually applied. However, problems with the trunk remain even after such an intervention. To overcome this challenge, combining other intervention methods with an exercise is suggested during training. Objectives: To investigate the effect of breathing based abdominal draw-in technique on the thickness of the transversus abdominis muscle and trunk control in stroke patients. Design: Randomized controlled study. Methods: After designating a group that will perform the abdominal draw-in technique as Experimental Group I and another group that will perform the breathing based abdominal draw-in technique as Experimental Group II, the thickness of the transversus abdominis muscle and the trunk impairment scale (TIS) of the subjects were measured as pre-tests before the interventions and as post-tests after the six week intervention period. Results: In the within group comparison, there was a significant change in the thickness of the transversus abdominis muscle for both groups while the subjects performed the abdominal draw-in technique; a significant change was also noted in their TIS (P<.05) (P<.01). However, in the inter-group comparison, a significant difference was found only in the TIS between the two groups (P<.05). Conclusion: After the application of the breathing based abdominal draw-in technique, an efficient contractile response was observed even in the muscles around the abdomen of the subjects, which indicates that this technique is an intervention method that can more effectively improve trunk control.